Pengaruh Kualitas Pelayanan Tendik dan Kinerja Dosen Terhadap Kepuasan Mahasiswa - Icha Apriliza (Bildung: Jurnal Ilmu Pendidikan, 2025)
This research investigates the influence of academic support service quality and lecturer performance on student satisfaction at the Sekolah Tinggi Ilmu Tarbiyah (STIT) Az Zahra Tasikmalaya. Grounded in the increasing demand for quality assurance in higher education, this study highlights how well-executed academic services and competent lecturers are crucial determinants of student trust and institutional credibility. Employing a quantitative approach, data were collected from 100 student respondents selected through the Slovin formula, utilizing structured questionnaires, interviews, and observations. The validity and reliability of the instrument were confirmed through statistical testing, with subsequent data analysis conducted using SPSS version 24. The findings demonstrate that both academic service quality and lecturer performance significantly affect student satisfaction across three dimensions: teaching effectiveness, administrative service delivery, and the adequacy of learning infrastructure. The study concludes that sustained improvements in service responsiveness, information accuracy, accessibility, and facility provision are essential to enhancing overall student satisfaction. These insights provide practical implications for institutional policy-making and strategic quality enhancement in higher education